2011
DOI: 10.1002/met.246
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of occurrence of daily summer monsoon precipitation over Karnataka

Abstract: Karnataka, a State in south peninsular India, receives 73% of its annual rainfall during the southwest monsoon season. Because of the complex physiographical features, the rainfall pattern over the State shows large spatial variation from 50 to 350 cm. The co-efficient of interannual variation of the monsoon rainfall is about 15% over coastal Karnataka (CK) and between 20 and 30% over interior Karnataka. It is, therefore, a difficult task to predict the location specific daily rainfall over Karnataka. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Also, the relative humidity and maximum daily temperature had the highest correlation of the occurrence of daily precipitation. The results are also agree with Agnihotri & Mohapatra (2012), which examined the forecast of daily summer monsoon rains in the Karnataka region of India and concluded that the highest correlation of daily rainfall is with relative humidity parameters and minimum daily air temperature.…”
Section: Discussionsupporting
confidence: 87%
“…Also, the relative humidity and maximum daily temperature had the highest correlation of the occurrence of daily precipitation. The results are also agree with Agnihotri & Mohapatra (2012), which examined the forecast of daily summer monsoon rains in the Karnataka region of India and concluded that the highest correlation of daily rainfall is with relative humidity parameters and minimum daily air temperature.…”
Section: Discussionsupporting
confidence: 87%
“…About 40 million hectares (almost 12% of the area) of India are susceptible to floods (Husain 2012). India receives 75% of the rain during the S-W monsoon season (June-September) (Agnihotri and Mohapatra 2012). Most of the rivers overflow during this period, resulting in intense recurring floods.…”
Section: Introductionmentioning
confidence: 99%
“…Other methods focus on investigating the relationship between local precipitation and large-scale atmosphere circulations, which vary from linear regression (e.g., [30][31][32][33][34][35]) to complex nonlinear models (e.g., [36][37][38][39][40]). Although numerous studies were carried out, a general standardized precipitation downscaling method still does not exist, especially for complex terrains.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have used stepwise regression for different purposes. For example, Harpham and Wilby[39], Hessami et al[42], and Huth[66] adopted Stepwise for predictor selection; Agnihotri and Mohapatra[30] applied it to occurrence estimation of daily summer monsoon precipitation. In this study, stepwise regression is adopted to test LASSO.…”
mentioning
confidence: 99%